Analysis of the role and motivation of human capital in the post-pandemic period of COVID-19 - Widya Adhariyanty Rahayu; Adriani Kala’lembang (Менеджмент та підприємництво: тренди розвитку, 2023)
In this era of globalization, human capital as human capital is a determining factor in ensuring social and cultural progress. Human capital is able to develop itself and contribute to understanding the problems that exist in science and high technology, social, and modern economy. In creating quality education, it is determined by the role of human capital, namely the teacher as a role holder in the world of education who has the ability of intellectual capital to transfer knowledge. The quality of human capital will determine the quality of the transfer of knowledge. This study uses qualitative research so that it will produce descriptive data. This study was carried out in a Junior High School in the Malang district. 67% of human capital has carried out skills development in the form of online learning media training, 50% participated in training dissemination from teachers who had attended training, and as many as 33% had never participated in scientific activities. This shows that the quality and motivation of teachers as human capital in self-development is quite high.